Winston Spencer Churchill - De Muynck, Gust (Brussel : Manteau, 1944)
Bibliotheek Camille Huysmans
Dedicator: De Muynck, Gust, dedicatee: Anseele (jr.), Edward, dedicatee: Huysmans, Camille
Nederlands
Monografie
Keywords: Churchill, Winston